The Relationship between Occupationally Exposed Arsenic, Cadmium and Lead and Brain Bioelectrical Activity—A Visual and Brainstem Auditory Evoked Potentials Study - Marta Waliszewska-Prosół; Maria Ejma; Paweł Gać; Anna Szymańska-Chabowska; Magdalena Koszewicz; Sławomir Budrewicz; Grzegorz Mazur; Małgorzata Bilińska; Rafał Poręba (Brain Sciences, 2021)
The aim of this study was to evaluate the parameters of visual and brainstem auditory evoked potentials in patients occupationally exposed to arsenic, cadmium and lead. The study group comprised 41 copper smelter and refinery workers (average age: 51.27) with occupational exposure to arsenic, cadmium and lead. The control group consisted of 36 healthy volunteers (35 men and 1 woman, aged 27–66, average age: 51.08). Neurological examination, brain imaging, and visual and brainstem auditory evoked potentials were performed, and the relationship between blood Cd, Pb concentration (Cd-B, Pb-B), blood zinc protoporphyrin (ZnPP), and urine As concentration (As-U) were assessed. In the workers, exceedances of allowable biological concentrations were observed, with the urinary concentration of arsenic being 5.2%, the cadmium and lead in blood being 1.3%, while the case of ZnPP was 2.6%. The mean P100, relative P100, and N145 visual evoked potential (VEP) latencies were significantly longer in exposed workers than in the controls. The mean wave III and V brainstem auditory evoked potential (BAEP) latency and the mean wave III–V and I–V interpeak latencies were longer, and the I and V amplitude was lower in the workers than the controls. In summary, occupational exposure to As, Cd, and Pb is associated with prolonged latency and reduced evoked potential amplitude, but As-U, Pb-B, Cd-B, and ZnPP concentrations are not linearly related to potential components. The analysis of evoked potentials may be a useful method of assessment of the central nervous system in patients with occupational exposure to heavy metals.